Non-verbal communication: aspects observed during nursing consultations with blind patients Comunicación no-verbal: aspectos observados durante la consulta de Enfermería con el paciente ciego Comunicação não-verbal: aspectos observados durante a consulta de Enfermagem com o paciente cego - Cristiana Brasil de Almeida Rebouças; Lorita Marlena Freitag Pagliuca; Paulo César de Almeida (Universidade Federal do Rio de Janeiro, 2007)
Exploratory-descriptive study on non-verbal communication among nurses and blind patients during nursing consultations to diabetes patients, based on Hall's theoretical reference framework. Data were collected by recording the consultations. The recordings were analyzed every fifteen seconds, totaling 1,131 non-verbal communication moments. The analysis shows intimate distance (91.0%) and seated position (98.3%); no contact occurred in 83.3% of the interactions. Emblematic gestures were present, including hand movements (67.4%); looks deviated from the interlocutor (52.8%), and centered on the interlocutor (44.4%). In all recordings, considerable interference occurred at the moment of nurse-patient interaction. Nurses need to know about and deepen non-verbal communication studies and adequate its use to the type of patients attended during the consultations. Estudio exploratorio y descriptivo sobre comunicación no-verbal entre el enfermero y el paciente ciego durante la consulta de enfermería al diabético, desde el referencial teórico de Hall. Colecta de datos con filmación de la consulta, analizadas a cada quince segundos, totalizando 1.131 momentos de comunicación no-verbal. El análisis muestra alejamiento íntimo (91,0%) y postura sentada (98,3%), en 83,3% de las intervenciones no hubo contacto. Estubo presente el gesto emblemático mover las manos (67,4%); el mirar desviado del interlocutor (52,8%) y al mirar centrado en el interlocutor (44,4%). En todas las filmaciones, hubieron interferencias considerables en el momento de la interacción enfermero y paciente. Concluyese que el enfermero precisa conocer y profundizar los estudios en comunicación no-verbal y adecuar su utilización al tipo de pacientes asistidos durante las consultas. Estudo exploratório-descritivo sobre comunicação não-verbal entre o enfermeiro e o cego durante a consulta de enfermagem ao diabético, a partir do referencial teórico de Hall. Coleta de dados com filmagem da consulta, analisadas a cada quinze segundos, totalizando 1.131 momentos de comunicação não-verbal. A análise mostra distância íntima (91,0%) e postura sentada (98,3%); em 83,3% das interações não houve contato. Esteve presente o gesto emblemático de mover as mãos (67,4%); o olhar desviado do interlocutor, (52,8%) e o olhar centrado no interlocutor (44,4%). Em todas as filmagens, houve interferências consideráveis no momento da interação enfermeiro-paciente. Conclui-se, que o enfermeiro precisa conhecer e aprofundar os estudos em comunicação não-verbal e adequar o seu uso ao tipo de pacientes assistidos durante as consultas.